Celebritization of Polish politics, and the language of comments and Internet entries. Analysis of selected examples - Scheffs, Łukasz; Sulikowska, Aleksandra (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
This article deals with the possible manifestations of the ongoing process of the celebritization of politics in the view of the language of comments that occur on gossip websites which, in fact, have become the places of the deliberate image-creation of people related to politics. The means of creation comes down to publishing content associated with the private or semi-private lives of people who are engaged in politics. In addition, we can also observe a far-reaching process of the vulgarization and brutalization of the language of comments and entries which is also a specific phenomenon.

Artykuł traktuje o możliwych przejawach postępującego procesu celebrytyzacji polityki z uwzględnieniem języka komentarzy, jakie pojawiają się na plotkarskich portalach internetowych. Te ostatnie także stają się bowiem miejscem specyficznie rozumianej kreacji wizerunkowej osób/podmiotów związanych z polityką. Sam sposób tej kreacji sprowadza się do publikowania treści związanych raczej ze sferą prywatną lub półprywatną, a na pewno niemającą związku z aktywnością tych osób/podmiotów na arenie politycznej. Dodatkowo obserwować daje się także daleko posunięty proces wulgaryzacji i brutalizacji języka tych komentarzy, co również jest zjawiskiem specyficznym.
Celebrytyzacja polskiej polityki i język komentarzy internetowych. Analiza na wybranych przykładach
Keywords: celebritization; celebrytyzacja; brutalization; brutalizacja; the language of politics; język polityki